KAJIAN YURIDIS PERAN HUKUM DAN KEBIJAKAN PERSAINGAN USAHA DALAM OPTIMALISASI POTENSI UMKM GUNA MEWUJUDKAN EKONOMI YANG SEIMBANG DAN BERKEADILAN - Yuniarti, Rahmi; Cheny Berlian (LPPM, Universitas Muhammadiyah Riau, 2023)
The role of business competition is very important in the context of market balance in order to make a perfect market, in this case run by the Business Competition Supervisory Commission (KPPU). In relation to business competition laws and policies, KPPU has the task of supervising the implementation of MSME partnerships. The problem that the author will examine is the role of competition law and policy in optimizing the potential of SMEs in order to create a balanced and just economy. The approach method that will be used is normative juridical which is focused on conducting a juridical analysis related to business competition law and MSMEs. The research results obtained are the role of law and business competition policy towards optimizing MSMEs in accordance with the objectives of the establishment of Law 5 of 1999, one of which is, creating a conducive business climate through regulation of fair business competition so as to ensure certainty of equal business opportunities for large business actors., medium business actors, and small business actors and so on, to create effectiveness and efficiency in business activities.